ANALISIS KINERJA BIDANG PENGEMBANGAN POTENSI DAN KEMITRAAN DINAS KEBERSIHAN DAN PERTAMANAN KOTA SEMARANG DALAM PENANGANAN KEBERSIHAN DI KOTA SEMARANG - Tri Wijaya Kusuma; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2016)
This study aims to determine the performance of Bidang Pengembangan Potensi dan Kemitraan Dinas Kebersihan dan Pertamanan Kota Semarang and describe the factors that support and hinder performance. This study uses five dimensions of organizational performance assessment with qualitative descriptive approach. Data collection techniques that used were observation, interviews, documentation and literature study with the informants from employees of Bidang Pengembangan Potensi dan Kemitraan Dinas Kebersihan dan Pertamanan Kota Semarang. Based on the discussion the results of the study, researchers concluded that the performance of Bidang Pengembangan Potensi dan Kemitraan Dinas Kebersihan dan Pertamanan Kota Semarang has been well. This is shown with the clarity of access, timetables and mechanisms of the program of activities and services that systematic implementation of the tasks according to the procedure, have an open attitude in responding to the needs of society, the principles of transparency and have a proactive attitude in promoting the success of hygiene management program. It's just that they found some blocks that cause the performance of Development Potential and the Partnership is not maximized, such as budget constraints and infrastructure, shortage of collectors levy and the lack of public participation which led to delay of some programs, such as the cooperation of business, marketing products waste utilization and achievement of the target of retribution. To overcome these problems, there are some suggestions that can be done, such as optimizing the aplication of budget, infrastructure and human resources that available now, preparating and implementating the activities program that can minimize the minimize of the budget and infrastructure, optimizing the number and capabilities of the existing levy collectors, cooperating with 3rd party in the billing and admission charges activities, and improve the knowledge, ability and awareness of the good waste utilization and the importance of abiding to pay the levy.